2010
DOI: 10.4162/nrp.2010.4.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake and snack choice by the meal patterns of employed people

Abstract: The aim of this study was to provide descriptive information on meal and snack patterns and to investigate snacks in relation to energy intake and food choice according to the meal patterns of employed people in Korea. 683 employed people (292 males, 391 females) were interviewed to collect one day dietary data by using 24-h dietary recall. A recorded day was divided into 3 meal and 3 snack periods by the respondent's criteria and the time of consumption. To analyze the eating pattern participants were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Similar to the findings in our study, dinner was an important source of fish and vegetables, while snacks contributed substantially to fruit intake. Other studies have also found that fruits are a common component of snacks (18)(19)(20)(21) . However, the contribution of different meal types to intakes of different food items is likely to vary in different populations and population subgroups, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings in our study, dinner was an important source of fish and vegetables, while snacks contributed substantially to fruit intake. Other studies have also found that fruits are a common component of snacks (18)(19)(20)(21) . However, the contribution of different meal types to intakes of different food items is likely to vary in different populations and population subgroups, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Among the meal skippers who consumed less than 3 meals a day, 22 respondents were frequent snack eaters (≤2M+2,3S) and 24 respondents were infrequent snack eaters (≤2M+0,1S). Compared to the study by Kim and Kim (2010), the most common meal pattern was three meals plus one snack (3M+1S) observed in 24.2% of the respondents who were employed people in Korea. Association between meal and snacking patterns and energy and nutrient intakes: The mean daily energy intake was 1654 kcal, and the protein, fat and carbohydrate intakes were 66.5 g, 220.9 g and 56.3 g respectively.…”
Section: Meal and Snacking Patternsmentioning
confidence: 99%
“…Previous studies show that frequent snacking influences the intake of macronutrients included carbohydrate, protein, fat and micronutrients such as calcium, folate and iron (Bellisle 2003 ;Kim and Kim, 2010 ;Whybrow and Kirk 1997]. Besides, according to Hampl et al, 2003), multiple snackers had more prudent energy-adjustedintakes of protein, cholesterol, calcium and sodium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), adults aged 45–75 in the UK (Titan et al . ) and men and women aged 20–65 years in Korea (Kim & Kim ). A similar relationship was also found with fat and/or protein intakes in some (Edelstein et al .…”
Section: Introductionmentioning
confidence: 99%